3D printing assisted conceptual design of biodegradable PLA surgical staple with self-tightening function - Yeo, Eugene Jun Hao (2014)
Shape memory materials (SMMs) are materials that possess the ability of recovering to its original shape from a seemingly plastic deformation when a particular stimulus is applied. This unique property of SMM is termed as shape memory effect (SME). This exclusive SME property can be used widely in many fields of work, namely biomedical field that is of relevance to the report.